2015
DOI: 10.4238/2015.november.13.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IGF-1 rs35767 and rs972936 polymorphisms with the risk of osteoporosis in a Chinese postmenopausal female population

Abstract: ABSTRACT. The aim of our study was to conduct a case-control study in a Chinese postmenopausal population to evaluate the roles of the IGF-1 rs35767 and rs972936 polymorphisms on bone mineral density (BMD) levels and osteoporosis risk. A total of 272 consecutive postmenopausal women with a primary diagnosis of osteoporosis and 272 controls were enrolled in the study between 2012 and 2014. The polymerase chain reaction-restriction fragment length polymorphism method was used to genotype the rs35767 and rs972936… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Among these, 4 case-control studies met the inclusion criteria and were included in the final analyses. [ 23 26 ] Figure 1 summarizes the process of identifying eligible studies. All of the studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 4 case-control studies met the inclusion criteria and were included in the final analyses. [ 23 26 ] Figure 1 summarizes the process of identifying eligible studies. All of the studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2807 participants took part in the studies, with 1 recruiting men and women, [ 25 ] and 3 women only. [ 23 , 24 , 26 ] Four studies investigated rs35767, [ 23 26 ] 3 studies assessed rs2288377, [ 23 25 ] and 3 studies evaluated rs5742612. [ 23 25 ] The pooled minor allele frequency for rs35767, rs2288377, rs5742612 was 0.291 (95% CI: 0.275–0.308), 0.100 (95% CI: 0.088–0.113), and 0.131 (95% CI: 0.118–0.146), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six studies, five [ 17 , 25 – 27 , 29 ] referred to rs35767, rs2288377, and rs5742612. While Wei et al’s study [ 28 ] focused on rs35767 and rs972936. Three studies [ 25 , 27 , 29 ] reported both male and female participants, yet the remaining three studies [ 17 , 26 , 28 ] focused on the association in only post-menopausal women subjects.…”
Section: Resultsmentioning
confidence: 99%
“…While Wei et al’s study [ 28 ] focused on rs35767 and rs972936. Three studies [ 25 , 27 , 29 ] reported both male and female participants, yet the remaining three studies [ 17 , 26 , 28 ] focused on the association in only post-menopausal women subjects. The genotype frequencies of both case and control groups were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation